Certification of Services in the Managerial System of Ecotourism Development - BELONOZHKO, Marina L.; KIRICHUK, Stepan M.; SILIN, Anatoly N. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).19, 2019)
The relevance of the study is determined by the fact that eco-tourism today is nothing more than a set of proposals on the tourism market, which is an important component of the country's tourist complex, but does not always meet international requirements for the provision of tourist services. The novelty of the research lies in the formation of requirements for certification of services in the country's eco-tourism as the basis for compliance of the proposed services with international requirements. The article provides a comparative analysis of all proposed criteria for the evaluation of tourism services. The authors adapt the proposed assessment of the ecological tourist complex. Solutions are proposed for determining the conformity of the service being provided on the Russian market to international standards, which will make it possible to introduce categories of services and the possibility of providing them. The authors claim that this will contribute to economic incentives for the analyzed industry. The practical significance of the study is determined by the possibility of forming supply in the tourist services market in the international community. The application of the obtained developments will form a competitive offer in the domestic market, since it is the attraction of foreign tourists and the correlation with the international standards of the service provided that will form the opportunity for the development of the industry.